Digital Marketing Internship at Counterpoint Research - Seenivasan, Dharshini (ATLAS SkillTech University, 2024)
This internship report provides a comprehensive overview of my tenure as a Digital Marketing Intern, focusing on my contributions to the effective dissemination of content across multiple platforms. The internship allowed me to work closely with a dynamic marketing team and gain valuable insights into the world of digital marketing. The report begins by presenting an overview of the company and its core business activities. The primary focus of my internship revolved around content management, ensuring timely and seamless publishing of content across diverse platforms. This involved developing an understanding of the target audience, tailoring content to their preferences, and coordinating with various teams to deliver engaging and relevant material. Additionally, the report highlights my responsibilities in managing the company's portal, which included uploading reports and intelligence trackers, contributing to the enhancement of the portal's user experience and overall accessibility. This played a crucial role in strengthening the company's online presence and positioning as a reliable source of industry insights. Another significant aspect of my internship was assisting with Search Engine Optimization (SEO) and website optimization. I engaged in keyword research, on-page and off-page optimization, and other SEO best practices to enhance the company's visibility on search engines. Moreover, the report touches upon my contributions to video and graphics content. Working alongside the creative team, I provided support in conceptualizing and executing captivating visual content that resonated with the target audience, reinforcing the company's brand identity.
Project Report on Digital Marketing Internship at Counterpoint Research (2022-24) Under the Guidance of Prof. Parag Amin
Keywords: Search Engine Optimization (SEO); website optimization; SEO; Digital Marketing; Marketing